Large-scale heat pumps: Uptake and performance modelling of market-available devices. (March 2021) - Jesper, Mateo; Schlosser, Florian; Pag, Felix; Walmsley, Timothy Gordon; Schmitt, Bastian; Vajen, Klaus
Abstract: Heat pumps powered by renewable electricity have a significant potential to become a critical technology to disruptively decarbonize industry. An essential step towards this goal is the development of an accurate understanding and model of how heat pumps in large-scale implementations perform in terms of economics, energy, and the environment. In this study, the influence of system design and operating conditions on the coefficient of performance (COP) of large-scale (>50 kWth ) electric driven mechanical compression heat pumps is reviewed. The review underscores the knowledge gap on the capabilities of large-scale heat pumps, especially the lack of simple mathematical COP-models based on real-world data. Developing and transferring a reliable COP-model and a comprehensive overview on capabilities of market available heat pumps to academics and practitioners (e.g. research engineers, energy-managers and consultants) can close this knowledge gap. Therefore, this study assembles a comprehensive dataset for the system configuration and performance of 33 large-scale heat pumps from 11 different manufacturers and addresses three main objectives: (1) Classifying and evaluating the capabilities of market available heat pumps. (2) Modelling the correlation between the COP and the operating conditions. (3) Developing an economic and ecological evaluation method for a heat pump project. Applying the developed models to accurately assess real-world performance and build a sound business case for large-scale heat pumps has the potential to accelerate the uptake of renewable energy and help improve overall environmental sustainability. Highlights: Summaries the potential and capabilities of market available heat pumps. Examines the influence of system configuration on heat pump efficiency. Develops accurate models for estimating the COP depending on operating conditions. Presents a short-cut method for economic and ecological feasibility assessment.